STRATEGI KOMUNIKASI MAPALA SAKAI DALAM MENINGKATKAN MINAT CAVING TERHADAP MAPALA DI PEKANBARU - Rafiq, M.; Firdaus, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Mapala Sakai itself is the first mapala caving pioneer in Riau. The science of caving is currently very common among nature-loving students in Pekanbaru, as a result nature-loving students are less concerned with the condition of existing karst areas. So the lack of availability of complete data and information regarding existing karst areas, results in management and policy making regarding karst and its contents being undirected and tending to ignore the important function and potential of karst as a never-ending water provider as well as being a repository of knowledge from various fields such as, biology, geology, hydrology, archeology, and also speleology. To maintain and preserve the karst areas in Indonesia, there is a need for cavers (cave exploration activists) who will study the science of caving and speleology. This research explains how Mapala Sakai's communication strategy increases interest in caving for mapala in Pekanbaru, and finds out what are the supporting and inhibiting factors of Mapala Sakai's communication strategy. This research method is descriptive qualitative, using a strategic communication model, in this research involving four informants in order to obtain relevant data, in accordance with the objectives and needs of the research using purposive sampling techniques. Based on research with informants, the results of this research show that Mapala Sakai's communication strategy in increasing interest in caving for Mapala in Pekanbaru is based on communication elements, namely communicator selection, message selection, media selection, audience selection, and response. These results were obtained from data processing using qualitative data analysis techniques. This research shows that Mapala Sakai, through a communicator selection strategy, targets audiences including active members of Mapala in Pekanbaru. The media used are social media such as YouTube and Instagram and direct face-to-face meetings, and the response is an increasing number of mapala members in caving activitie